Pocket kings [compact disc, unabridged] : a novel - Heller, Ted (Highbridge Audio, 2012)
Frank Dixon's first novel, Plague Boy, is sinking into oblivion on Amazon, and neither his nor anyone else's literary agent will return his calls. Then Frank discovers online poker, and is soon addicted to the rush he feels as the successful, popular 'Chip Zero.' But as he wins thousands of dollars, it soon becomes clear that his Internet success is not the solution to his problems. And when the virtual world comes crashing in on Frank's real life, it can only mean trouble.